História da psicologia social e comunicação de massa: leituras a partir de uma historiografia crítica - Conceição, Maria Flor Oliveira (2011)
This work seek understand the historical relations between Social Psychology and Mass Communication. There are a small number of studies about this subject that involves these mutual contributions in the first half of the Twenty Century, especially between 1920 and 1950 decades. To understand these connections was realized a specific research about the history of the two main perspectives of Mass Communication on period, the American Mass Communication Research and the Critical Theory of Frankfurt School and also locate their positions as parts of distinct traditions in Social Psychology. It was prepared the analyses of two special articles: The Effects of Mass Communication of Carl Hovland (1954) and On popular music of Adorno & Simpson (1941). In the articles can be found evidences that methods of Social Psychology was used for the study of the observed phenomenon in Mass Communication